The Impact of Life Satisfaction on Self-Care Engagement Among Patients with Type 2 Diabetes - Worek, Dominika; Ziemiańska, Joanna; Stanisławska, Marzena; Bąk, Ewelina (Journal of Education, Health and Sport, 2026)
Introduction: Self-care in type 2 diabetes refers to the daily management of the disease by the patient, that is, the actions patients take to control the disease and maintain their health. It includes, among other things, glucose monitoring, following a diet, taking medications, engaging in physical activity, and attending regular medical visits and follow-up examinations. Life satisfaction, on the other hand, is a subjective sense of contentment with one’s own life. Among people with type 2 diabetes, it depends on health status, disease control, mental well-being, and social support. Objective of the Study: The objective of the study was to investigate the relationship between life satisfaction and the level of engagement in self-care among patients with type 2 diabetes. Materials and Methods: The study was conducted on a group of 100 patients at the “Vita” Health Clinic in Kamesznica between September of 2025 and January of 2026. The study was conducted using a diagnostic survey method. The researchers used a self-designed questionnaire and standardized Self-Care of Diabetes Inventory (SCODI), and the Satisfaction with Life Scale (SWLS). Results: It was demonstrated that patients with type 2 diabetes exhibit greater autonomy in self-care with regard to self-confidence, and the lowest level of autonomy in terms of controlling their health status. The extent of glucose control and health behaviors are at a moderate level. In the study group, life satisfaction was average, with a tendency toward lower scores. The results also showed that the higher the level of life satisfaction, the higher the level of self-care among patients in all areas—namely, health behaviors, health status control, and glucose control—as well as a higher level of self-confidence. Conclusions: A higher level of life satisfaction promotes good self-care in type 2 diabetes. Both sociodemographic and clinical factors influence patients’ life satisfaction and engagement in self-care.